The reformist thought of Imam Musa Al-Kadhim (peace be upon him): A comparative study between Arab and Oriental scholars - Al-Badiri, Huda Naji (Al-Adab Journal, 2019)
The imams of the Ahl al-Bayt led the list of reformers in the world, so Imam al-Kadhim (peace be upon him) was concerned with reforming the affairs of people, even his enemies, in a way that represented peace and tranquility, as he was not convulsive with those who tried to undermine him. Whatever the researcher has broad knowledge in psychology, and no matter how proficient he is in sociology, and no matter how superior he is in all sciences, he cannot fully grasp the reality of the imams of the Ahl al-Bayt (peace be upon them) with their subjective phenomena and individual creations, and in fact what has affected them Their distinctive characteristics and unique tendencies in their personal and reform behavior make them in the highest ranks of humanity.